Comparison of emotional intelligence and cognitive ability in students with and without a faking response - Mahdiye Aali; Hassan Mahmoudian (مطالعات روانشناسی تربیتی, 2022)
the present study aims to compare the emotional and emotional intelligence among students with a faking response .the research method used in this study was Comparative causality. The population of 20,000 students from the Faculty of Psychology and Education was studying in the 1399 - 1400 Open University of South- Tehran. In this research, a sample of 295 students was selected using available sampling in two groups of pretend (149 people) and normal (146 people).They completed emotional intelligence questionnaires of Shot et a(1998) and Nejati cognitive ability (2012). Data were analyzed using multivariate analysis of variance. Considering the significance of F in the variable of emotional intelligence (F=8.730 and p<0.05) and the significance of the value of F in the variable of cognitive ability (F=10.773 and p<0.05), the results of variance analysis showed that the emotional intelligence and cognitive ability of students pretended to answer And normally there is a difference. The average emotional intelligence and cognitive ability in the faking group is higher than the normal group (p<0.05). Therefore, it can be said that in the self-report scales, it seems that the respondents have the ability to faked and this ability has a positive relationship with the cognitive ability and emotional intelligence of people, therefore it is necessary to select people and use personality tests should be done according to people's cognitive ability and emotional intelligence.